“She’s Surrounded by Loved Ones, but Feeling Alone”: A Relational Approach to Loneliness - Valenzuela-Garcia, Hugo (2021)
Loneliness poses one of the significant problems of our modern post‐industrial societies. Current research on loneliness has been developed primarily by psychology, biomedicine, nursing, and other health‐related disciplines, showing a surprising number of variables and risk factors involved in the experience of loneliness, along with positive correlations with premature mortality and morbidity. However, most of these analyses overlook the social interactions and context in which loneliness is experienced. Drawing on a subsample (N = 24) of Spanish “mothers” from impoverished families, the article proposes a mixed‐method approach (both relational and interpretative) that may potentially complement quantitative approaches, showing relational and contextual factors that may contribute to a better understanding of the subjective dimension of loneliness.